2019
DOI: 10.1080/23802359.2019.1674703
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the complete mitochondrial genome of Lucanus chengyuani (Coleoptera: Lucanidae)

Abstract: We sequenced and assembled the complete mitochondrial genome of Lucanus chengyuani, from the Alishan, Chiayi County, Taiwan. The length of the complete mitogenome of L. chengyuani is 16,926 bp and the mitogenome contains 13 protein-coding, 22 tRNA, and 2 rDNA genes. Nucleotide compositions of the whole mitogenome of L. chengyuani are 38.37% for A, 27.96% for T, 23.03% for C, and 10.637% for G. The AT and GC skewness of mitogenome sequence are 0.157 and-0.368, showing the Askew and C-skew. The reconstructed phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(19 reference statements)
2
4
0
Order By: Relevance
“…Additionally, in these five species of Prosopocoilus, we also detected an intergenic spacer of 18 bp between trnS2 (UCN) and nad1 with the conserved motif (TACTAAA), similar to other reported lucanid beetles [4,20,[50][51][52][53][54]. The IGS between trnS2 (UCN) and nad1 is common in Coleoptera mitogenomes, but varies in length [4,20,23,[50][51][52][53][54]. The characteristics of the large IGS between trnI and trnQ are only present in the representatives of this genus among the family Lucanidae; therefore, we propose that this feature may be synapomorphic for the members of the genus Prosopocoilus.…”
Section: Intergenic Spacerssupporting
confidence: 86%
See 3 more Smart Citations
“…Additionally, in these five species of Prosopocoilus, we also detected an intergenic spacer of 18 bp between trnS2 (UCN) and nad1 with the conserved motif (TACTAAA), similar to other reported lucanid beetles [4,20,[50][51][52][53][54]. The IGS between trnS2 (UCN) and nad1 is common in Coleoptera mitogenomes, but varies in length [4,20,23,[50][51][52][53][54]. The characteristics of the large IGS between trnI and trnQ are only present in the representatives of this genus among the family Lucanidae; therefore, we propose that this feature may be synapomorphic for the members of the genus Prosopocoilus.…”
Section: Intergenic Spacerssupporting
confidence: 86%
“…In these five Prosopocoilus mitogenomes, the short sequence (TAAAA) appeared four times (P. castaneus and P. laterotarsus), five times (P. blanchardi), and three times (P. confucius and P. astacoides), and the length of the intergenic region between the repetitive sequence (TAAAA) differed among these five species (Figure 4). Additionally, in these five species of Prosopocoilus, we also detected an intergenic spacer of 18 bp between trnS2 (UCN) and nad1 with the conserved motif (TACTAAA), similar to other reported lucanid beetles [4,20,[50][51][52][53][54]. The IGS between trnS2 (UCN) and nad1 is common in Coleoptera mitogenomes, but varies in length [4,20,23,[50][51][52][53][54].…”
Section: Intergenic Spacerssupporting
confidence: 84%
See 2 more Smart Citations
“…The evolutionary rates of PCGs in the mitochondrial genome of Dorcus showed that their evolution is based upon purifying selection [ 31 , 33 , 40 , 50 ]. Additionally, IGS studies have helped to resolve phylogenetic uncertainties, clarify evolutionary lineages, and provide insights into the diversification and biogeography of Lucanidae [ 27 , 36 , 40 ]. The previously reported Dorcus velutinus complex also has large IGSs and a short sequence (TACTAAATT), which could provide a unique phylogenetic signal in the genus Dorcus [ 31 , 40 ].…”
Section: Discussionmentioning
confidence: 99%